Patient Knowledge Regarding Radiation Exposure from Orthopaedic Foot and Ankle Imaging. Issue 3 (14th September 2018) - Bohl, Daniel; Manning, Blaine; Holmes, George; Lee, Simon; Lin, Johnny; Hamid, Kamran
Category: Other Introduction/Purpose: Foot and ankle surgeons routinely prescribe diagnostic imaging that exposes patients to potentially harmful ionizing radiation. The purpose of this study is to characterize patients' knowledge regarding radiation exposure associated with common forms of foot and ankle imaging. Methods: A survey was administered to all new patients prior to their first foot and ankle clinic appointments. Patients were asked to compare the amount of harmful radiation associated with chest x-rays to that associated with various types of foot and ankle imaging. Results were tabulated and compared to actual values of radiation exposure from the published literature. Results: A total of 890 patients were invited to participate, of whom 791 (88.9%) completed the survey. The majority of patients believed that a foot x-ray, an ankle x-ray, a "low dose" CT scan of the foot and ankle (alluding to cone-beam CT), and a traditional CT scan of the foot and ankle all contain similar amounts of harmful ionizing radiation to a chest x-ray (Table 1). This is in contrast to the published literature, which suggests that foot x-rays, ankle x-rays, cone beam CT scans of the foot and ankle, and traditional CT scans of the foot and ankle expose patients to 0.006, 0.006, 0.127, and 0.833 chest x-rays worth of radiation. Conclusion: The results of the present study suggest that patients greatly over-estimate the amount of harmful ionizing radiation associated with plain film and cone-beam CT scans of the foot and ankle. Interestingly, their estimates of radiation associated with traditional CT scans of the foot and ankle were relatively accurate. Results suggest that patients may benefit from increased counseling by surgeons regarding the relatively low risk of radiation exposure associated with plain film and cone-beam CT imaging of the foot and ankle.